The Effect of Using Interactive Multimedia-Based Learning Media to Improve Learning Outcomes in MI Al-Khairat Students, Hampalit village, Katingan District: Pengaruh Penggunaan Media Pembelajaran Berbasis Multimedia Interaktif terhadap Peningkatan Hasil Belajar Siswa MI Al-Khairat Desa Hampalit Kabupaten Katingan - Qamaruddin, Muhammad; Zannah, Fathul; Arnisyah, Siti (CV Aisha Edutama, 2024)
The interactions that occur during the learning process at MI AL-Khairat, Empalit Village, Katingan Regency, are influenced by the learning environment, including the effectiveness of the learning media. This research examines Multimedia which is a new technique in the field of multimedia, one of which is computers which combines more than one media in a form of communication which includes text, sound, graphics, animation and video into a computer system. The use of multimedia such as computers in the teaching and learning process at MI AL-KHAIRAT Hampalit village has practical values, including that media can arouse new desires and interests. By using media, children's learning experiences become broader, their perceptions become sharper, and their concepts become more complete, so that new desires and interests in learning always arise. Media can arouse motivation and stimulate students to learn. Posting pictures on bulletin boards, showing films and listening to audio programs can cause certain stimuli towards the desire to learn.